A preliminary exploration of executive retention in a Malaysian public research and development organization - Taib, Anita; Suandi, Turiman; Krauss, Steven Eric; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This paper is about an experience of conducting a first interview of an executive in a Malaysian public research and development organization. The purpose of this phenomenological interview is to explore the executive’s experience on his decision to stay with the organization from the Human Resource Development perspective. It is a first hand experience from the interviewee’s own language. The findings may provide better understanding why people stay in their current position especially in a public research and development organization by using phenomenological case study approach. A descriptive steps taken in conducting a phenomenological interview and problems throughout the interview is discussed and will be a guide to improve in the future interviews with other future relevant respondents of this study. The researcher ends with practical suggestions from her experience in conducting future interviews. The findings show pattern of codes and categories in accordance to the research questions through the researcher’s analytic lens. These findings are summarized in a matrix form to show how it fits in the theory used and will be used to develop a code book and thus developing the themes that will lead towards the development of theory.